A spring-clean of Michael Porter's Attic: The Canadian telecommunications sector as an exemplar of refurbished generic strategy. Issue 3 (18th May 2015) - Gould, Anthony M.; Desjardins, Guillaume
Abstract : Purpose: – This paper views the phenomenon of offering/user interface complexity as having competitive strategy-related consequences. Porter's conception of generic management strategy was created in the 1980s. It is not well adapted to industries which have proliferated in the Internet age. Accordingly, the conception presented in this article offers a modified version of Porter's generic strategy framework. The new view incorporates the dimension of complexity alongside the original dimensions of "target market" and "type of advantage". The article uses an analysis of the contemporary Canadian Telco sector to prosecute its case. Design/methodology/approach: – The project uses an analysis of the stated competitive positioning orientations of firms operating in the contemporary Canadian Telecommunications sector to build a case about the changed nature of generic strategy in the digital age. It uses inductive reasoning to generalise findings about the Telco sector to other recently emerged (digital-age) industries. Findings: – A revised view of Porter's generic strategy grid is presented and defended. Research limitations/implications: – The study analyses only one sector, but draws many broad conclusions. It uses inductive reasoning which is limited by the extent to which the exemplar case (telecommunications) may be compared to other cases within the same category (other digital age industries). The study does not use an extensive analysis of strategic planning documents of individual firms; however, this is not a limitation unless and until a critique challenges the claims made about generic strategies being pursued. Practical implications: – The new conceptualisation may be used as a planning tool for digital-age firms. Originality/value: – The project is a genuinely new attempt to update Porter's view of generic strategy. It overcomes the problems which have been associated with previous attempts at such revision.